Some Transaction Cost Effects of Authoritarian Management - Aleksandar Vasilev; Tamara Todorova (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the transaction-cost economizing effects of authoritarian management in organizations and systems subject to higher transaction costs originating from various sources. We analyze the nature, mechanisms and transaction-cost aspects of the authoritarian management style. We argue that the higher the transaction costs of internal organization, the more autocratic the manager is likely to be. We study the features of authoritarian managers in general but more specifically in the context of high transaction cost systems such as East European societies with significant transactional or organizational opportunism as well as other sources of market failure.
Keywords: D23; L23; M12; 330; authoritarian management; transaction costs; opportunism; multidivisional structure; information transfer